The Effect Of Worklife Balance, Organizational Climate And Compensation On Motivation And Its Impact On Employee Performance - Muhamad Anang Munawir (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
This study aims to determine and analyze the effect of work-life balance, organizational climate and compensation on motivation and its impact on employee performance. The results of this writing are expected to provide additional information or input for Algifari University in addressing labor issues and being able to manage and improve human resources in order to achieve maximum performance. The research method used is descriptive analysis and verification. The data collection used was interviews and questionnaires accompanied by observation and literature techniques, the sampling technique used simple random sampling. Field data collection will be carried out in 2023. The data analysis technique uses Path Analysis. The results of the study show that in general, work-life balance, organizational climate, compensation, motivation and employee performance fall into a fairly good category. Worklife balance, organizational climate and compensation have an effect on motivation both partially and simultaneously and motivation has an effect on employee performance partially. Worklife balance has more dominant influence on motivation.